General Principles and Challenges of Public Administration Organization in Austria - Bruneder, Antonia; Zankel, Maximilian (General Principles and Challenges of Public Administration Organization in Central Europe, 2024)
This chapter provides an overview of the Austrian administration, focusing on bodies at the federal, state and municipal levels. Furthermore, it elucidates the guiding principles of the administration, which can essentially be derived directly from the Federal Constitution. Subsequently, it also refers to current and future developments related to right to information and transparency issues. Austria is one of the few countries that continues to provide official confidentiality under the Federal Constitution. The abolition of official confidentiality and the possible right to information have long been part of political discourse. This topic is currently back on the agenda, and will likely trigger significant changes.KEYWORDS Austria, public administration, Federal Constitution, principles of administration, Federal administration, State administration, Municipal administration, administrative bodies, right to information, official confidentiality, transparencyBibliographyBarth, J., Ennöckl, D. (2019) ’Ein Volk muss sich bewaffnen mit der Macht des Wissens… – Plädoyer für ein Informationsfreiheitsgesetz, wie Alfred Noll es gefordert hat’, Journal für Rechtspolitik, 27(4), pp. 176–185 [Online]. Available at: https://doi.org/10.33196/jrp201904017601 (Accessed: 19 October 2024).Bauer, W. (2012) ’Amt der Landesregierung‘ in Pürgy, E. (eds.) Das Recht der Länder Band I Landesverfassungsrecht und Organisationsrecht. 1st edn. Vienna: Jan Sramek Verlags KG, pp. 423–442.Baumgartner, G. (2022) ’Untersuchungsausschüsse und Datenschutz Teil 1‘, Juristische Blätter, 144(4), pp. 201–211 [Online]. Available at: https://doi.org/10.33196/ jbl202204020101 (Accessed: 19 October 2024).Berka, W. (2021) Verfassungsrecht. 8th edn. Vienna: Verlag Österreich.Bezemek, C. (2020) ‘Zum Gegenstand von Untersuchungsausschüssen gemäß Art 53 Abs 2 B-VG‘ in Baumgartner, G. (eds.) Jahrbuch Öffentliches Recht. 1st edn. Vienna: Neuer Wissenschaftlicher Verlag, pp. 65–84.Ermacora, F. (ed.) (1990) Die Entstehung der Bundesverfassung 1920, Bd IV. Die Sammlung der Entwürfe zur Staats- bzw. Bundesverfassung. 1st edn. Vienna: Wilhelm Braunmüller.Grabenwarter, C., Holoubek, M. (2022) Verfassungsrecht – Allgemeines Verwaltungsrecht. 5th edn. Vienna: Facultas.Heinzle, C. (2017) ‘Schutz von Persönlichkeitsrechten durch den Verfassungsgerichtshof im Verfahren nach Art 138b Abs 1 Z 7 B-VG‘ in Baumgartner, G. (eds.) Jahrbuch Öffentliches Recht. 1st edn. Vienna: Neuer Wissenschaftlicher Verlag, pp. 101–120.Holoubek, M. (2014) ’Österreich’ in von Bogdandy, A., Cassese, S., Huber, P.M. (eds.) Handbuch Ius Publicum Europaeum. Band V: Verwaltungsrecht in Europa: Grundzüge. 1st edn. Heidelberg: C. F. Müller, pp. 435–475.Kahl, A. (2005) ’Art 52’ in Korinek, K., Holoubek, M., Bezemek, Ch., Fuchs, C., Martin, A., Zellenberg, U.E. (eds.) Österreichisches Bundesverfassungsrecht. Kommentar. 7th edn. Vienna: Verlag Österreich, pp. 1–29.Leeb, D. (2021) ’Art 83/2’ in Korinek, K., Holoubek, M., Bezemek, Ch., Fuchs, C., Martin, A., Zellenberg, U.E. (eds.) Österreichisches Bundesverfassungsrecht. Kommentar. 16th edn. Vienna: Verlag Österreich, pp. 1–34.Leitl-Staudinger, B. (2011) ’Österreich’ in von Bogdandy, A., Cassese, S., Huber, P.M. (eds.) Handbuch Ius Publicum Europaeum. Band IV: Verwaltungsrecht in Europa: Wissenschaft. 1st edn. Heidelberg: C. F. Müller, pp. 195–228.Lukan, M. (2018) Die Kreation von Verwaltungsorganen. 1st edn. Vienna: Verlag Österreich. Merkl,A. (1927) Allgemeines Verwaltungsrecht. Neudruck von Robert Walter 1999. 1st edn. Vienna: Verlag Österreich.Muzak, G. (2020) Bundes-Verfassungsrecht. 6th edn. Vienna: Manz Verlag.Olechowski, T. (2019) Rechtsgeschichte. Vienna: Facultas. Olechowski, T. (2020) ‘Hans Kelsens Verfassungsentwürfe‘ in Jabloner, C., Olechowski, T., Zeleny, K. (eds.) Die Verfassungsentwicklung 1918-1920 und Hans Kelsen. 1st edn. Vienna: Manz Verlag, pp. 157–166.Öhlinger, T., Eberhard, H. (2022) Verfassungsrecht. 13th edn. Vienna: Facultas.Pürgy, E. (2012) ’Bezirksverwaltungsbehörden‘ in Pürgy, E. (ed.) Das Recht der Länder Band I Landesverfassungsrecht und Organisationsrecht. 1st edn. Vienna: Jan Sramek Verlags KG, pp. 443–462.Raschauer, B. (2000) ’Art 20/1’ in Korinek, K., Holoubek, M., Bezemek, Ch., Fuchs, C., Martin, A., Zellenberg, U.E. (eds.) Österreichisches Bundesverfassungsrecht. Kommentar. 3rd edn. Vienna: Verlag Österreich, pp. 1–52.Raschauer, B. (2021) Allgemeines Verwaltungsrecht. Lehrbuch für Fortgeschrittene. 6th edn. Vienna: Verlag Österreich.Steiner, W. (2012a) ’Landesregierung‘ in Pürgy, E. (ed.) Das Recht der Länder Band I Landesverfassungsrecht und Organisationsrecht. 1st edn. Vienna: Jan Sramek Verlags KG, pp. 299–383.Steiner, W. (2012b) ‘Landeshauptmann‘ in Pürgy, E. (ed.) Das Recht der Länder Band I Landesverfassungsrecht und Organisationsrecht. 1st edn. Vienna: Jan Sramek Verlags KG, pp. 385–421.Trauner, G. (2016) ’Teil 4 – Wahlen zum Gemeinderat’ in Pabel, K. (ed.) Das österreichische Gemeinderecht. 1st edn. Vienna: Manz Verlag, pp. 1–95.Weilguni, J. (2017) ’Teil 6 – Wahl und Abberufung der Mitglieder des Gemeindevorstands und der Gemeinde(rats)ausschüsse‘ in Pabel, K. (ed.) Das österreichische Gemeinderecht. 1st edn. Vienna: Manz Verlag, pp. 1–61.Wiederin, E. (2010) ’Österreich’ in von Bogdandy, A., Cassese, S., Huber, P. (eds.) Handbuch Ius Publicum Europaeum. Band III: Verwaltungsrecht in Europa: Grundlagen. 1st edn. Heidelberg: C. F. Müller, pp. 187–228.Wieser, B. (2001a) ’Art 20/3’ in Korinek, K., Holoubek, M., Bezemek, Ch., Fuchs, C., Martin, A., Zellenberg, U.E. (eds.) Österreichisches Bundesverfassungsrecht. Kommentar. 18th edn. Vienna: Verlag Österreich, pp. 1–47.Wieser, B. (2001b) ’Art 20/4’ in Korinek, K., Holoubek, M., Bezemek, Ch., Fuchs, C., Martin, A., Zellenberg, U.E. (eds.) Österreichisches Bundesverfassungsrecht. Kommentar. 18th edn. Vienna: Verlag Österreich, 1–47.Wieser, B. (2024a) Vergleichendes Verfassungsrecht. 3rd edn. Vienna: Verlag Österreich.Wieser, B. (2024b) Einführung in das Verfassungs- und Verwaltungsrecht. 5th edn. Vienna: Verlag Österreich.Ziehensack, H. (2023) Amtshaftungsgesetz – Praxiskommentar. 2nd edn. Vienna: Verlag LexisNexis.